EFEKTIVITAS PEMANFAATAN WEBSITE PEMERINTAH KOTA KENDARI SEBAGAI MEDIA INFORMASI PUBLIK - La Tarifu; Taufik; Nani Eka Pertiwi (Halu Oleo University, 2022)
This study aims to determine the Effectiveness of Utilization of the Kendari City Government Website as a Public Information Media. The method used in this study is qualitative, the informants in this study were five people. Data collection techniques are interviews, observation and documentation. The data analysis used is data reduction, data presentation, data verification and drawing conclusions. The results of this study indicate that the use of the Kendari City government website as a medium of public information, namely; The role of the Kendari City Government website has been quite effective in providing information to the public. The government's own role for the website is quite effective where the role of the website is as a manager, regulator, controller and supervisor. For interactions within the Kendari City Government website have not yet occur directly in the website but through the portal of the application available in it, for example between the government with the community, government with business environment, government with government, and government with employees.